BALI MAWACARA: IS A QUASI-COMMON LAW SYSTEM DEVELOPING IN BALINESE CUSTOMARY LAW? - Kelly, Danial; Windia, Wayan P (Indonesia Law Review, 2019)
The Indonesian island of Bali is internationally renowned as a popular tourist destination. Tourists from around the world have been attracted to Bali’s rich and colourful displays of culture and its friendly people for many decades. Intertwined with the predominately Hindu culture that is so readily visible is the invisible customary legal system of Bali that regulates much of the daily life of the Balinese. This autochthonous legal system exists in plurality with the Indonesian state legal system. As with all legal systems, the Balinese customary law system is in a state of flux. This article will examine the foundational sources and purposes of authority in the Balinese customary law system and analyse the pressures of change upon that system. It will be argued that an embryonic quasi-common law system is developing in the Balinese customary law system due to the recent formation of the Majelis Utama Desa Pakraman and the Bali mawacara jurisprudence.